The Chilean education reform and its impact on quality. An economic vision - Icochea, Olympia (Universidad del Pacífico, 1993)
The author studies Chile's educational reforms in the eighties, and assesses their successes and failures in terms of quality of teaching. The reforms rested principally on two aspects: decentralized administration (municipal authorities assuming responsibility) and the application of market economic mechanisms for financing schools. Chile's democratic government subsequently added a number of measures that the reforms lacked, such as increasing outlay to the sector and improving educational quality in subsidized schools. However, the success of these reforms is still uncertain.